Polyamide-nylon 6 particulate polycarbonate composites with outstanding energy-absorbing properties. (21st July 2022) - Kim, Min-Kyeom; Kim, Hyung-Ick; Nam, Jae-Do; Suhr, Jonghwan
Abstract: As there are gradually increasing interests in polymeric energy-absorbing materials to reduce unwanted noise/vibration, and enhance impact resistance in structural applications, considerable efforts have been empirically made to improve energy-absorbing properties. However, there has been no detail understanding of the energy-absorbing mechanisms of particulate composites, thereby showing a trade-off between toughness and modulus/strength. Therefore, by coupling modeling and experimental efforts, this study systematically explores the thermoplastic polymer particle toughening and ways to overcome the typical compromise in energy-absorbing composites. Polyamide-nylon 6 particulate polycarbonate composite was carefully designed for achieving extraordinary energy absorption with the uncompromised properties. The debonding, fracture toughness and yieldings were semi-empirically investigated to reveal fracture energy contributions. It was found that the mainly responsible energy-absorbing mechanism was matrix yielding (48.28%), which results from the particle debonding and significantly contribute to crack propagations. This study could provide new solutions for the energy-absorbing composites without any comprome in modulus/strength. Graphical abstract: Energy absorbing mechanism (particle debonding, crazing, void nucleation and growth, subsequent matrix yielding, and crack behaviors) and fracture energy contribution of the polyamide-nylon 6 particulate polycarbonate composite. Note that main energy absorbing mechanism is matrix yielding. Image 1 Highlights: PC/PA6 composite exhibits extraordinary uncompromised and energy-absorbing properties. Thermoplastic particle-toughening mechanism was semi-empirically investigated. Crack impeding and deflection by the yielding and particles enhanced fracture energy. Main mechanism of toughness improvement was matrix yielding by particle debonding.